Calculation Of Sedimentation Rate at Sempor Reservoirs in 2018 Using Modified Universal Soil Loss Equation Method (MUSLE) - Septi Arini; Yulaikhah Yulaikhah; Bambang Kun Cahyono (Jurnal Geospasial Indonesia, 2019)
Sempor Reservoir located in the Telomoyo River Basin in the Serayu River region is categorized as one of the priority watersheds based on the 2015-2019 Strategic Plan of the Ministry of Environment and Forestry. Priority watershed is a watershed that gets more attention in controlling water pollution, one of which is sedimentation. Watershed observation and management activities are needed for the reservoir to operate optimally. One of the observations and management activities of the Sempor Watershed is the calculation of sedimentation rate. In this research the sedimentation rate was calculated using the MUSLE method that included runoff parameter, erodibility, slope, land cover and conservation factor. The Sempor watershed boundary is obtained through delineation of DEM. The calculation is done by utilizing a Geographic Information System (GIS) through analysis of soil type maps, length and slope maps,  land cover and conservation maps with the boundaries of the Sempor Reservoir. Based on this result, the Sempor Reservoir has a sedimentation rate of 166,173,500 tons/year and a sedimentation thickness rate of 3,7259 mm/year. According to the provisions of the Ministry of Forestry in 2009, the rate of sedimentation thickness in the Sempor Reservoir is included in the medium class. The river as one of the potential means of sediment transport contributes to the rate of sediment thickness of 3.7256 mm /year, while for areas outside the river coverage it only 0.003 mm/year. The river has a major influence on sedimentation in the Sempor Reservoir.